MANAJEMEN KONFLIK DI TENGAH DINAMIKA PONDOK PESANTREN DAN MADRASAH - Firman Asirullah; Fikrul Mustanir Wahid; Arif Eka Rahmansyah; Mu’allimin, Mu’allimin (BADAN PENERBIT STIEPARI PRESS, 2022)
Recently, the public in the Maya world has been stirred up by many cases that have occurred in educational institutions, especially Islamic educational institutions, especially Islamic boarding schools, which require their students to live in cottages. Admittedly or not, Islamic educational institutions, especially Islamic boarding schools and madrasas, have the possibility of conflict is quite high compared to educational institutions another. From this assumption, this paper aims to analyze the role of management conflict in resolving conflicts that occur within the scope of educational institutions Islam. Based on theoretical studies, it can be concluded that conflict management become very central in developing conflicts that exist in institutions Islamic boarding school and madrasa education as a way to develop Islamic educational institutions for the better. Besides, since it has become the inevitability that conflict cannot be avoided, then control the conflict become a necessity in order to achieve goals in Islamic educational institutions.